The Prognostic Value of the Advanced Lung Cancer Inflammation Index on Disease-Free Survival in Patients with Gastric Cancer Receiving Neoadjuvant Chemotherapy - Mahmut Kara; Muslih Ürün; Senar Ebinç; Yasin Sezgin; Yonca Yılmaz Ürün; Mehmet Naci Aldemir (Journal of Clinical Medicine, 2026)
Objectives: The present study investigated whether the pre-treatment Advanced Lung Cancer Inflammation Index (ALI) could serve as a prognostic indicator of disease-free survival (DFS) in patients with locally advanced gastric cancer treated with neoadjuvant chemotherapy followed by curative D2 gastrectomy. Methods: We retrospectively analyzed 157 patients with gastric adenocarcinoma who received treatment between 2016 and 2025. The pre-treatment ALI was derived from body mass index, serum albumin concentration, and the neutrophil-to-lymphocyte ratio. The association of clinical and laboratory variables with DFS was assessed using Kaplan–Meier survival analysis and Cox proportional hazards regression. Results: Median patient age was 63.6 years (61.1% male). Overall, 50.3% of patients experienced recurrence. Multivariate analysis demonstrated that ALI is an independent prognostic factor for DFS (HR = 0.867; 95% CI: 0.768–0.978; p = 0.020). Advanced age (p = 0.040), advanced clinical N stage (p < 0.001), and non-FLOT regimens (p = 0.003) also significantly predicted poorer DFS. Kaplan–Meier analysis confirmed that median DFS was significantly shorter in the low ALI group (38.9 months) compared to the high ALI group (52.0 months; p = 0.029). Conclusions: A low pre-treatment ALI score independently predicts shorter DFS in locally advanced gastric cancer patients treated with neoadjuvant chemotherapy and surgery. ALI serves as an accessible, low-cost biomarker to identify high-risk patients, warranting further prospective validation.